2013
DOI: 10.1016/j.amjoto.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound characterization of middle ear effusion

Abstract: Purpose To further enhance and assess the ability to characterize middle ear effusion (MEE) using non-invasive ultrasound technology. Materials and Methods This is a prospective unblinded comparison study. Fifty-six children between the ages of 6 months and 17 years scheduled to undergo bilateral myringotomy with pressure equalization tube placement were enrolled. With the child anesthetized, the probe was placed into the external ear canal after sterile water was inserted. Ultrasound recordings of middle ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The severity of the lesion in the middle ear cavity varies, as the consistency of MEE changes in patients with OME . In this study, we found that the concentration of pepsin gradually increased when the viscosity of the middle ear cavity fluid increased.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The severity of the lesion in the middle ear cavity varies, as the consistency of MEE changes in patients with OME . In this study, we found that the concentration of pepsin gradually increased when the viscosity of the middle ear cavity fluid increased.…”
Section: Discussionmentioning
confidence: 56%
“…The severity of the lesion in the middle ear cavity varies, as the consistency of MEE changes in patients with OME. 31 In this study, we found that the concentration of pepsin gradually increased when the viscosity of the middle ear cavity fluid increased. These data suggest that pepsin aggravates OME, and that MEE appearing in the middle cavity is likely caused by pepsin, because the pepsin level in the dry ear subgroup was significantly lower than that in the serous and ear mucoid subgroups.…”
Section: Discussionmentioning
confidence: 63%
“…Compared with the results of previous studies10111314 the proposed Nakagami approach uses the mastoid as an acoustic window, thus allowing physicians to simply position an ultrasound probe on the mastoid and transmit an ultrasound pulse into the mastoid to determine MEE. Such a noninvasive technique allows patient comfort during examination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the advantages of ultrasound in assessing MEE91011121314. The previously proposed ultrasound technique involves positioning an ultrasound probe in front of the tympanic membrane through the external ear canal.…”
mentioning
confidence: 99%
See 1 more Smart Citation